Emprendimiento industrial y desarrollo productivo para el crecimiento economico del canton Babahoyo - Marquez Valero, Rosario Margoth (2015)
In Ecuador a state policy is changing the productive matrix, for which there is support for the development of new factors of production, enabling Ecuadorians contribute to the socioeconomic development of the country and in turn develop its economic family. This has led to propose the development of a study entitled INDUSTRIAL PRODUCTION UP AND DEVELOPMENT FOR ECONOMIC GROWTH BABAHOYO CANTON, which aims to organize the productive activities carried out in the canton independently and in different urban and marginal sectors of this city.